Trends in agile and cooperative manufacturing - Leitão, Paulo (2010)
This paper discusses the actual state of the manufacturing systems, focusing on the paradigms, requirements and problems for control and supervision. Based on the experience of the authors in those fields, a new approach to agile, distributed and cooperative manufacturing systems is presented and discussed. This new approach is based on a multi-agent platform that supports three main components: control and cooperation, communication, and re-engineering.